Genetic diversity and gene flow in collapsed and healthy abalone fisheries - K. J. MILLER; B. T. MAYNARD; C. N. MUNDY (Molecular Ecology, 2009)
Overexploitation of marine species invariably results in population decline but can also have indirect effects on ecological processes such as larval dispersal and recruitment that ultimately affect genetic diversity and population resilience. We compared microsatellite DNA variation among depleted and healthy populations of the black‐lip abalone Haliotis rubra from Tasmania, Australia, to determine if over‐fishing had affected genetic diversity. We also used genetic data to assess whether variation in the scale and frequency of larval dispersal was linked to greater population decline in some regions than in others, and if larval dispersal was sufficient to facilitate natural recovery of depleted populations. Surprisingly, allelic diversity was higher in depleted populations than in healthy populations ( P 0.05). Significant subdivision across hundreds of metres among our sampling sites ( F ST = 0.026, P